Plasma polyunsaturated fatty acid profile is associated with vascular endothelial function in patients with type 2 diabetes - Morioka, Tomoaki; Emoto, Masanori; Imamura, Satoshi; Kakutani, Yoshinori; Yamazaki, Yuko; Motoyama, Koka; Mori, Katsuhito; Fukumoto, Shinya; Shioi, Atsushi; Shoji, Tetsuo; Inaba, Masaaki (Diabetes & vascular disease research, 2018)
Decreased plasma n-3 polyunsaturated fatty acid levels or the n-3/n-6 polyunsaturated fatty acid ratios are associated with a risk of cardiovascular events. In this cross-sectional study, we measured plasma levels of eicosapentaenoic acid, docosahexaenoic acid, and arachidonic acid and investigated the association between the plasma polyunsaturated fatty acid profile and vascular endothelial function in 396 patients with type 2 diabetes. Endothelium-dependent, flow-mediated dilatation of the brachial artery was measured using ultrasonography. Multiple regression analyses, including age, sex, body mass index, and other cardiovascular risk factors, revealed that plasma eicosapentaenoic acid levels (β = 0.140, p = 0.008) and the eicosapentaenoic acid/arachidonic acid ratio (β = 0.127, p = 0.019), but not plasma docosahexaenoic acid levels (β = 0.067, p = 0.220) or the docosahexaenoic acid/arachidonic acid ratio (β = 0.034, p = 0.559), were independently and positively associated with flow-mediated dilatation. In conclusion, plasma eicosapentaenoic acid levels and the eicosapentaenoic acid/arachidonic acid ratio are independently associated with endothelial function in patients with type 2 diabetes. This study indicates a positive association between eicosapentaenoic acid, rather than docosahexaenoic acid, and endothelial function in type 2 diabetes.